2019
DOI: 10.3389/fpsyt.2019.00105
|View full text |Cite
|
Sign up to set email alerts
|

Problematic Use of Mobile Phones in Australia…Is It Getting Worse?

Abstract: Rapid technological innovations over the past few years have led to dramatic changes in today's mobile phone technology. While such changes can improve the quality of life of its users, problematic mobile phone use can result in its users experiencing a range of negative outcomes such as anxiety or, in some cases, engagement in unsafe behaviors with serious health and safety implications such as mobile phone distracted driving. The aims of the present study are two-fold. First, this study investigated the curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
63
2
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(74 citation statements)
references
References 55 publications
3
63
2
6
Order By: Relevance
“…Although problematic mobile phone use has been explored throughout Australia [ 38 ], our study is the first to explore nomophobia among an Australian sample. This study consists of the second largest sample size ( n = 2838) in any nomophobia study to date [ 31 ], revealing a mean nomophobia score of 69.4 (moderate) among respondents.…”
Section: Discussionmentioning
confidence: 99%
“…Although problematic mobile phone use has been explored throughout Australia [ 38 ], our study is the first to explore nomophobia among an Australian sample. This study consists of the second largest sample size ( n = 2838) in any nomophobia study to date [ 31 ], revealing a mean nomophobia score of 69.4 (moderate) among respondents.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed the negative effects of bedtime blue light-emitting-device use on sleep due to its association to cognitive stimulation [1,4,6,7,[14][15][16][17][18] and/or to problematic excessive use [9,[18][19][20][21][22][23][24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…It is assumed that impaired sleep leads to many serious consequences in health as overweight/obesity or mood disorders and increased accidents [1,2,[4][5][6][7][8][9][10][11][12][13]. Appropriate behavior and environment are thus critical to achieve adequate quality and quantity of sleep.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the results of this experience highlight the explanatory link between latent factors and actual behaviors reported by children, and this has been a common constraint to the performance of further predictions in merely descriptive studies, which usually employ smaller or excessively local samples. Nevertheless, it is worth remarking two potential shortcomings related (respectively) to the structural analysis and the contents of the instruments we used: first that-although significant-the Standardized Path Coefficients (SPCs) remain considerably low in magnitude (which does not invalidate the results but suggests their careful interpretation) and, second, that for this study we did not consider in depth the emergence of new factors that could potentially get involved in the road safety dynamics of children, and which may also threaten or compromise their behavioral performance, such as cellphones and other information and communication technologies [55,56]. It is noticeable how the use of technological devices has been progressively becoming more and more frequent in the young populations, as part of other research and interventions in the field of Education for Road Safety, and should be therefore considered in further studies addressing a similar research problem.…”
Section: Discussionmentioning
confidence: 99%